2016
DOI: 10.5007/1980-0037.2016v18n4p391
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Performance Level of Fencers on Simple and Choice Reaction Time

Abstract: -In many sport disciplines reaction time plays a key role in the sport performance. It is good to point out for example ball games or fighting sports (fencing, karate etc.). The research is focused on detection of the differences in the simple and choice reaction time during visual stimulation among elite, sub-elite fencers and beginners. For the measurement a Fitrosword device and the SWORD software were used. An additional stimulus was added during measuring which should increase the overall number of stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
20
1
1
Order By: Relevance
“…Measurements of the bioelectric signal employed a 16-channel EMG system manufactured by Noraxon (DTS, Desktop Direct Transmission System, Noraxon, Scottsdale, ZA, USA) with a sampling accuracy of 16 bits at a frequency of 1500 Hz. The analysis involved the following muscles: Biceps brachii (BB), triceps brachii (LT), flexor carpi ulnaris (FCU), extensor carpi radialis (ECR) on the upper limb holding the weapon, biceps femoris (BF), rectus femoris (RF) on the forward leg, and gastrocnemius as well as caput laterale and caput mediale (GL, GM) on the rear leg [3,11]. The muscle activation assessment applied Ag/AgCl electrodes attached to the subjects’ bodies in accordance with the SENIAM (surface EMG for non-invasive assessment of muscles) procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the bioelectric signal employed a 16-channel EMG system manufactured by Noraxon (DTS, Desktop Direct Transmission System, Noraxon, Scottsdale, ZA, USA) with a sampling accuracy of 16 bits at a frequency of 1500 Hz. The analysis involved the following muscles: Biceps brachii (BB), triceps brachii (LT), flexor carpi ulnaris (FCU), extensor carpi radialis (ECR) on the upper limb holding the weapon, biceps femoris (BF), rectus femoris (RF) on the forward leg, and gastrocnemius as well as caput laterale and caput mediale (GL, GM) on the rear leg [3,11]. The muscle activation assessment applied Ag/AgCl electrodes attached to the subjects’ bodies in accordance with the SENIAM (surface EMG for non-invasive assessment of muscles) procedures.…”
Section: Methodsmentioning
confidence: 99%
“…It was not until the 1930s that the flèche was introduced by Hungarian fencers and formed an innovative, dynamic solution in the attacks performed on a fencing strip leading to a touch [2]. For this reason, research in the field of biomechanics and motor control often applied the lunge as a diagnostic procedure in the area of comprehensive analysis [3,4,5]. Both touch techniques are fundamentally different in terms of the technique that is followed.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have indicated that the skill level of the athlete had no effect on reaction time. For example, Balko et al 25 observed no difference between the reaction times of elite and nonelite fencers. In soccer players, reaction time was not different among elite and nonelite athletes.…”
Section: -24mentioning
confidence: 99%
“…Therefore, these subjects do not need this interhemispheric transfer. The advantage in reaction times is the result of them compared with subjects with ipsilateral dominant eye and responding hand (Azémar et al, 2008;Balkó, 2016;Balkó, Borysiuk, Balkó, & Špulák, 2016). At the same time, the results prove that reaction time of elite and amateur athletes is the same (Balkó, Borysiuk, & Šimonek, 2017;Balkó, Wasik, Chytrý, Dunajová, & Škopek, 2017).…”
Section: Introductionmentioning
confidence: 96%